(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
The article examined the process of incorporation of the pre-Brooke polities and pre-state people in Sarawak through the perspective of the Sarawak native officers. It offers a historical view on the state-making and state formation in Sarawak during the rule of the Brooke rajahs. The article engages a method of historical reconstruction based on the official report and published works contemporary to the era. It has selected the first decade from the cession of Baram district (1883 to 1893) as a case study to emphasise the challenges faced by the Brooke state in enticing nonstate people into its territorial lines. The study found that the role of native officer was key in the process of incorporation. The theory of practice explained how communication between the native officer and the tribal elites was facilitated by social prestige and social class, indigenous to the political culture predating the Brooke’s modern state. This shows the continuation of the primordial political-economy culture into the construction of a modern, colonial state.